Pengembangan Bahan Ajar Matematika Realistik berbasis Alquran Pokok Bahasan Pecahan - Muhammad Ihsan (Suska Journal of mathematics Education, 2019)
AlQur'an-based realistic mathematics is an approach used in compiling fraction teaching materials, connecting mathematics with the Qur'an is an effort to make mathematics learning more meaningful and realistic. The focus of this research is how to develop Qur’an-based realistic Mathematics teaching material that is valid and practical fraction. This research is a development research that adopts the ADDIE model. However, in this study only did three stages, namely analysis, design and development. Teaching materials that have been designed are validated by three experts namely media experts, design experts and content experts as well as practicality tests by students through data collection techniques using questionnaires. The results of data analysis show that all validation results are in the "valid". While the level of practicality measured by the response questionnaire of students gets in the category "practical".